Fundamentos do controle do erro administrativo, pelo Tribunal de Contas, sob a égide da Lei de Introdução às Normas do Direito Brasileiro (LINDB) - Ariane Shermam Morais Vieira (2024)
The present thesis aims to understand the legal nature, characteristics and effects of the essential mistake, in the sense of the Section n. 28 of the Act of Introduction to the Norms of Brazilian legal system (LINDB), in view of the binding of public administration to legality. This LINDB provision stipulates that authorities and civil servants will only be personally responsible for their decisions and technical opinions in the case of intent and essential mistake. The following research problems guided the development of the investigation: how to characterize the administrative mistake based on the provisions of Section n. 28 of the Act of Introduction to the Norms of Brazilian legal system (Decree-Law n. 4.657/1942)? Does a mistake that is not essential constitute an illegality, a non-compliance with the legal system, but not punishable, or is it a legal species characterized by lawfulness? Is this a normative species included in legality? Does an authority mistake that is not classified as essential remove the punishment due to the absence of the conduct willful element (fault or intent)? How can the definition of mistake be made compatible with the constitutional power to sanction by the external control of public administration carried out by the Federal Court of Auditors? From the examination of the literature studied, a theoretical gap was identified regarding the legal nature and the assumptions for identifying administrative mistake in the Brazilian doctrine. It was observed that the lack of more in-depth studies on the topic reverberates in the jurisprudence of the Federal Court of Auditors. In this scenario, theoretical and empirical research was carried out, based on the analysis of scientific texts, in particular, studies of branches of legal dogmatics such as constitutional law and administrative law, in addition to legislation and jurisprudence related to the topic. The TCU jurisprudence was chosen as the object of analysis due to the national scope of its jurisdiction and the volume of data available. Based on the characterization of the administrative mistake, and given the theoretical premise that mistakes that are not essential are not punishable, the aim was to make them compatible with the sanctioning powers of the TCU, especially given the prevailing understanding in the Court's jurisprudence that the Section n. 28 does not apply to cases involving damage to the treasury. The study identified that this jurisprudence is not in line with the doctrinal position regarding the existence of a legal space for tolerance or accommodation of legally relevant mistakes. As a result of the investigation, it was concluded that the mistake involves illegal, omissive or commissive conduct. However, the presence of fault in a reduced degree reduces the reprehensibility of the conduct and is capable of ruling out punishment and/or determination of compensation for damage to the treasury, always based on the analysis of the circumstances of the specific case, based on legal requirements. It was also found that the analysis of the existence of the mistake and, above all, its effects, implies the concrete exercise of decision-making autonomy by the authority, based on an abstract legal provision. To summarize: considering the existence and punishability of a mistake as discussed in this research implies, as a rule, the recognition of the authority's exercise of discretionary powers.